PKM Pencegahan Covid-19 Varian Baru (Omicron) Desa Telukawur - Prastiwi, Bertika Kusuma; Ratimiasih, Yulia; Zhannisa, Utvi Hinda; Widiyatmoko, Fajar Ari (Universitas PGRI Semarang, 2022)
The second wave of the Covid-19 virus is still a problem in Indonesia. Many community activities are restricted including school, work, sports. However, many people ignore health protocols, thinking that the pandemic is over. People in Telukawur village also think that the pandemic is over. The people of Telukawur village have forgotten about the implementation of health protocols, it is proven that they rarely use masks, keep their hands clean and use hand sanitizer. From the above problems, the activities carried out were direct socialization to the Telukawur village community by distributing masks, installing appeal signs, socialization and exposure to the new variant of the COVID-19 virus to village organizations and demonstrations for making hansanitazers. From the activities carried out, it is hoped that the community will care about the health of themselves and others by preventing the spread of the COVID-19 virus, implementing health protocols and being independent in making natural hand sanitizers. As a result of the activities carried out, the Telukawur village community is more concerned about the health of themselves and others by implementing health protocols in their daily lives. The conclusion of this activity is that the pandemic is not over, people must continue to apply health protocols wherever they are.AbstrakVirus Covid 19 gelombang kedua masih menjadi permasalahan di Indonesia. Banyak kegiatan masyarakat yang dibatasi diantaranya sekolah, bekerja, berolahraga. Namun banyak masyarakat yang mengabaikan protokol kesehatan, beranggapan bahwa pendemi telah berakhir. Masyarakat di desa Telukawur juga beranggapan pendemi telah berakhir. Masyarakat desa Telukawur sudah melupakan mengenai penerapan protokol kesehatan, terbukti sudah jarang penggunaan masker, menjaga jarak mencuci tangan dan penggunaan handsanitazer. Dari permasalahan diatas maka kegiatan yang dilakukan adalah sosialisasi langsung kepada masyarakat desa Telukawur dengan cara pembagian masker, pemasangan plang himbauan, sosialisasi dan paparan mengenai virus covid 19 varian baru ke organisasi-organisasi desa serta demontrasi pembuatan hansanitazer. Dari kegiatan yang dilakukan diharapkan masyarakat peduli terhadap kesehatan diri sendiri dan orang lain dengan mencegah penyebaran virus covid 19, menerapkan protokol kesehatan dan kemandirian dalam pembuatan handsanitazer alami. Hasil dari kegiatan yang dilakukan, masyarakat desa Telukawur lebih peduli terhadap kesehatan diri sendiri dan orang lain dengan cara menerapkan protokol kesehatan dalam kehidupan sehari-hari.Â Kesimpulan kegiatan ini pendemi belum berakhir masyarakat harus tetap menerapkan protokol kesehatan dimanapun mereka berada.